Acellular scaffolds, cellular therapy and next generation approaches for knee cartilage repair - Pedro Debieux; Enzo Salviato Mameri; Giovanna Medina; Keng Lin Wong; Camila Cohen Keleka (Elsevier, 2024)
Introduction: Full-thickness knee cartilage defects are a potential source of significant morbidity for patients and incur an increased risk for early degenerative joint disease. Recent decades have seen several advancements in the field of cartilage repair, among which osteochondral allograft transplantation and autologous chondrocyte implantation stand out as the options with the most durable and effective results. There are several limitations, however, to the current generation of cartilage repair options, spanning from cost and availability-related issues to the inherent implications of 2-stage surgery, and potentially limited capacity for tissue regeneration. Objectives: The present review aims to offer an overview of next-generation approaches for cartilage repair, providing the rationale and available evidence for novel acellular scaffolds, cell-based therapies, mesenchymal stem cells, extra-cellularextracellular vesicles (exosomes), allogenic therapies, and gene therapies. Methods: This article reviews current literature regarding innovations in the repair of chondral and osteochondral injuries. Results: Emerging approaches the so-called next generation of cartilage repair are numerous and aim to harness the optimal biological environment and structural support needed to potentially enhance clinical outcomes. Conclusion: The next generation of care for cartilage injuries aims to enhance the quality of scaffolds, cell types, cell viability, and integration with the receptor; and to introduce new technologies such as three dimensional bioprinting scaffolds, acellular and gene therapies.